2013
DOI: 10.1039/c3cp52247d
|View full text |Cite
|
Sign up to set email alerts
|

Methanol to olefins: activity and stability of nanosized SAPO-34 molecular sieves and control of selectivity by silicon distribution

Abstract: Royal Society of ChemistryLi, Z.; Martínez Triguero, LJ.; Concepción Heydorn, P.; Yu, J.; Corma Canós, A. (2013 AbstractNanoSAPO-34 molecular sieve synthesized in microwave environment with 20nm of crystal size showed higher lifetime than SAPO-34 prepared by conventional hydrothermal method in the reaction of methanol to olefins. It has been found that silicon distribution strongly affects lifetime and selectivity. Thus, silicon at the border of the silicon islands gives higher lifetime and lower C2/C3 ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 63 publications
(117 reference statements)
6
112
0
1
Order By: Relevance
“…Moreover, the peak at 1651 cm −1 corresponds to the vibration of hydroxyl groups from adsorbed water on samples. In addition, the broad peak centered at 3445 cm −1 corresponds to Si\OH and P\OH groups interacting through H-bonds [15]. In comparison of SAPO-34-H-M and SAPO-34-V-M samples, the intensity of all the vibration bands for SAPO-34-L-M-T and SAPO-34-L-M is stronger.…”
Section: Ft-ir Spectroscopymentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the peak at 1651 cm −1 corresponds to the vibration of hydroxyl groups from adsorbed water on samples. In addition, the broad peak centered at 3445 cm −1 corresponds to Si\OH and P\OH groups interacting through H-bonds [15]. In comparison of SAPO-34-H-M and SAPO-34-V-M samples, the intensity of all the vibration bands for SAPO-34-L-M-T and SAPO-34-L-M is stronger.…”
Section: Ft-ir Spectroscopymentioning
confidence: 95%
“…Hydrothermal method, as the conventional strategy, has been applied in the preparation of SAPO-34 by numerous researchers [4][5][6][7][8][9][10][11][12][13][14][15]. However, separation between solvents and solid products is required by filtration or centrifugation, and partial organic SDAs are inevitably preserved in the liquid phase, resulting in the wastewater pollutants and downstream purification system installation [16].…”
Section: Introductionmentioning
confidence: 99%
“…4,[13][14][15][16] In the case of SAPO-34, its performance has been improved by developing mesopores [17][18][19][20][21][22] and by synthesizing crystals of smaller size. [23][24][25][26][27][28][29][30][31] The use of dual templates, which implies small organic struture directing agent for the formation of micropores and large organic molecular surfactants for developing mesopores as a strategy to prepare meso-MFI, has been proposed 32,33 . The large molecular surfactant hexadecyl trimethyl ammonium bromide (CTAB) firstly used to prepare MCM-41 has been employed to the synthesis of hierarchical zeolites in the dual template method.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported on the effect of the silicon content in the catalytic performance of SAPO catalysts. [31][32][33][34] The framework of microporous aluminophosphates is built up of AlO4 and PO4 tetrahedra connected through the oxygen atoms in an alternating arrangement. SAPO materials are formed by the isomorphous substitution of trivalent Al and pentavalent P atoms by tetravalent Si atoms.…”
Section: Introductionmentioning
confidence: 99%